The Effect of Planting Depth on the Vegetative Growth of Caulerpa racemosa in a Tarpaulin Tank Cultivation System - Ismail, Irwan; Dangeubun, Jane Lulinda; Madubun, Usman; Rahantoknam, Santi Penina Tua (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2025)
Caulerpa racemosa is a type of green macroalgae with high economic value that has the potential to be cultivated intensively. This study aimed to evaluate the effect of planting depth on the vegetative growth of Caulerpa racemosa cultivated in a tarpaulin tank system. Three planting depths were tested: 20 cm, 40 cm, and 60 cm. Vegetative growth parameters observed included Absolute Growth in Weight, Absolute Growth in Stolon Length, and Absolute Growth in Ramuli Length over a defined cultivation period. The results indicated that the 60 cm planting depth yielded the highest vegetative growth, with mean weight reaching 137.67±3.21 g, stolon length 30.04±0.54 cm, and ramuli length 25.29±2.90 cm. Statistical analysis revealed a significant difference only in stolon length between the 60 cm and 40 cm treatments, while differences in weight and ramuli length were not statistically significant. Overall, the data suggest that a 60 cm planting depth provides a more stable microenvironment in terms of light intensity, water temperature, and protection from physical disturbances, thereby enhancing biomass accumulation and vegetative structure development in Caulerpa racemosa. Therefore, a planting depth of 60 cm is recommended as the optimal depth for cultivating Caulerpa racemosa in tarpaulin-based culture systems.